Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai di Dinas Ketenagakerjaan Kota Lubuklinggau - Hardi Mulyono; Irma Idayanti; Maya Sandra Pertiwi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
The problem in this study is the effect of work discipline and work environment on the performance of employees at the Lubuklinggau City Manpower Department. This research methodology uses quantitative research and descriptive research design. By using data collection techniques: interviews (Interview), Observation, Documentation, and Questionnaires. The population in this study were 35 respondents. Simple linear regression test results found that partially in the first hypothesis (H1) there was an influence of work discipline on employee performance with the equation Y = 36,293 + 0.827, the correlation coefficient (R) being = 0.562, the T test obtained t value = 3.901> t table 1,692 and Sig. 0,000 <0.05 then Ho is rejected and Ha is accepted. The second hypothesis (H2) There is an influence of the work environment on employee performance with the equation Y = 47,937 + 0454, the correlation coefficient (R) being = 0.561, the T test obtained tcount = 3.892> t table 1.692 and Sig 0.000 <0.05 then Ho rejected and Ha accepted. And for the results of multiple linear regression testing shows that simultaneously in the third hypothesis (H3) there is an influence of work discipline and work environment on employee performance with the equation Y = 13,181 + 0.670 + 0.368, the coefficient of determination with the value of R square (R2) = 0.510 , obtained F Test with a value of F count 16.668> F table 3.29 and Sig 0.000 <0.05. Then Ho is rejected and Ha is accepted.